Covid-19 outbreak in Sabah: a prelimiary survey on its effects on hotel industry & some key concerns during pre-movement control order period - Rafiq Idris; Kasim Mansur; Rizal Zamani Idris; Mori Kogid (Human Resource Management Academic Research Society, 2020)
Malaysia was ranked the first position in the Global Muslim Travel Index 2019 (Global Muslim Travel Index, 2019). Besides, the Travel and Tourism Competitiveness Report 2019 ranked Malaysia at 29th out of 140 countries overall (Travel and Tourism Competitiveness Report, 2019). In the same report, from Travel and Tourism Policy and Enabling Conditions’ perspective, Malaysia was ranked at the 11th position (Travel and Tourism Competitiveness Report, 2019). Government of Malaysia has, among others, announced year 2020 as the Visit Malaysia Year to attract more tourists. The first month of the year had showed promising numbers of tourists’ arrivals. However, towards the end of January 2020, CoVID-19 outbreak presents the tourism industry with a major challenge. Following the outbreak, some countries have banned the arrival of tourists from certain countries. Accordingly, this has somehow affected the hotel industry. Based on feedbacks from hotel employees, this paper examines the preliminary effects on hotel industry in Sabah, Malaysia.